THE EFFECT OF PREGNANT WOMEN KNOWLEDGE ON COMPLIANCE WITH TRIPLE ELIMINATION EXAMINATION - Siti Aisah; Rahayu Khairiah (International Journal of Medicine and Health, 2023)
Background: According to WHO data, in Southeast Asia in 2015 the HIV rate reached 5.1 million patients with 77,000 pregnant women living with HIV, and 19,000 new cases of pediatric HIV infection have been found. This is a number that can be considered fantastic compared to other regions. Meanwhile for syphilis, the incidence rate has shown an increase of 0.32% in the Southeast Asian region. The number of patients shows up to 167,000 cases of syphilis in pregnant women. It had a disastrous impact by producing 65,800 adverse outcomes including early fetal death. For Hepatitis B, Southeast Asia bears 15% of the total number of Hepatitis B patients worldwide with a total of 39 million people. Prevention activities have been carried out by the Ministry of Health of the Republic of Indonesia by holding a program called Triple Elimination in accordance with WHO recommendations (2017). The activity was in the form of carrying out tests for HIV, Hepatitis B and Syphilis (triple Elimination) during Antenatal Care (ANC) for Pregnant. Research Objectives: to find out the factors that influence the triple elimination examination in pregnant women at the Sarageni Health Center, Lebak Regency in 2022. Research Methods: quantitative with cross sectional research design. The sample in this study was 65 pregnant women in the Sarageni Health Center area in November 2022 (Purposive Sampling). Data were collected using a questionnaire given to respondents then processed and analyzed univariate and bivariate and tested with the Chi Square test. The results of the study: the prevalence that affects the compliance of pregnant women Age p-value 0.006 <0.05 Education p-value 0.000 <0.05 Socio-economic p-value 1.000 >0.05 and Husband support p-value 0.000 <0.05.